A kiss for Little Bear - Minarik, Else Holmelund; Sendak, Maurice ([New York] : HarperCollinsPublishers, 1968)
Little Bear's thank-you kiss from grandmother gets passed on to him by many animals and greatly aids the skunks' romance.
100
Preschool-3--Jacket.
Accelerated Reader AR
Keywords: Bears -- Juvenile fiction; Animals -- Juvenile fiction